African Union Strategic Climate Investment Partnership Roundtable: Working Group Information Brief Series - Chevallier, Romy; Gosling, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
On 6 February 2022, the African Union’s (AU's) Climate Change and Resilient Development Strategy and Action Plan (2022-2032) was endorsed at the 35th Ordinary Session of the AU’s Assembly of African Heads of State and Government. This is Africa’s first collective climate change action plan and Strategy that details specific suggested actions the continent needs to urgently achieve to respond to climate change. Subsequently, on the 19-20 June 2023, the AU hosted a Strategic Climate Investment Partnership Roundtable in Addis Ababa, Ethiopia. The objective of the roundtable was to leverage partnerships and align investment opportunities to support the operationalisation of the Strategy. This series of information briefs was developed as reference materials for the Working Groups at the AU Roundtable event. The eleven briefs covered the thematic areas of the Strategy including governance and policy, the blue economy, digital transformation, energy systems, food systems, gender and youth inclusion, industrialisation, land-based ecosystems, transport, urbanisation and water systems. The information briefs provide context to the thematic areas, list the priority action areas and highlight the regional policy frameworks and flagship initiatives.